The enhancement on oil shale extraction of FeCl3 catalyst in subcritical water. (1st January 2022) - Kang, Shijie; Sun, Youhong; Qiao, Mingyang; Li, Shengli; Deng, Sunhua; Guo, Wei; Li, Jiasheng; He, Wentong
Abstract: The coupling effect of subcritical water and FeCl3 on the extraction of bulk Huadian oil shale was experimentally investigated. The results showed that, with the addition of FeCl3, the yield of shale oil in subcritical water extraction was enhanced by 58.5 % at 20 h and the time required for the maximum shale oil production was reduced by 43 %. The group compositions of shale oil and residual bitumen as well as the elemental analysis of residual kerogen revealed that FeCl3 could trigger the pyrolysis reaction networks of kerogen by promoting the cleavage of heteroatom bonds, and accelerate the decomposition of asphaltenes in residual bitumen. GC-MS analysis of n -alkanes in shale oil and residual bitumen showed that FeCl3 promoted the secondary cracking of saturated hydrocarbons in residual bitumen rather than in shale oil due to the adsorption of Fe 3+ in shale matrix. The solid-state 13 C NMR analysis of the residual kerogen indicated that the polycondensation of kerogen was inhibited and the ring-opening reaction of aromatic structure was promoted in the presence of FeCl3 . In addition, the acidic FeCl3 solution induced the decomposition of carbonate minerals in oil shale matrix to provide additional mass transfer channels for the migration of bitumen products. Graphical abstract: Image 1 Highlights: Combination of subcritical water and catalyst is proposed for oil shale extraction. The yield of shale oil was greatly enhanced with shortened extraction time. FeCl3 promotes the decomposition of kerogen by breaking the heteroatom bonds. FeCl3 promotes the further decomposition and migration of bitumen in shale matrix.